2008
DOI: 10.1152/ajpendo.00016.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac overexpression of hormone-sensitive lipase inhibits myocardial steatosis and fibrosis in streptozotocin diabetic mice

Abstract: Intracellular lipid accumulation (steatosis) and resultant lipotoxicity are key features of diabetic cardiomyopathy. Since cardiac hormone-sensitive lipase (HSL) is activated in diabetic mice, we sought to explore a pathophysiological function of cardiac HSL in the development of diabetic cardiomyopathy. Transgenic (Tg) mice with heart-specific HSL overexpression were generated, and cardiac histology, function, lipid profile, and gene expressions were analyzed after induction of diabetes by streptozotocin. Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 55 publications
6
45
2
Order By: Relevance
“…The mRNA expression of genes related to β-oxidation was downregulated (CPT-1, PPAR-a) or unchanged (ACO, UCP2) and those related to lipogenesis (SREBP-1, FAS, HMG-CoAR) was unchanged in the liver by angiotensin II infusion. These findings were in contrast to our previous findings that accumulation of TG occurred in the kidney and heart of the same animal model, 12,13 indicating that angiotensin II-induced lipid accumulation is somehow tissue-specific, which is different from the case of diabetes in which accumulation of excessive lipids can be seen in the liver 19 as well as the kidney 20 and heart, 21 and accompanied by a modulation of lipid metabolism-related genes in these tissues. 20,[22][23] We also found that oil red O-stainable lipid was increased in the liver (unpublished observations) as well as in the kidney and heart of the rat model of metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 99%
“…The mRNA expression of genes related to β-oxidation was downregulated (CPT-1, PPAR-a) or unchanged (ACO, UCP2) and those related to lipogenesis (SREBP-1, FAS, HMG-CoAR) was unchanged in the liver by angiotensin II infusion. These findings were in contrast to our previous findings that accumulation of TG occurred in the kidney and heart of the same animal model, 12,13 indicating that angiotensin II-induced lipid accumulation is somehow tissue-specific, which is different from the case of diabetes in which accumulation of excessive lipids can be seen in the liver 19 as well as the kidney 20 and heart, 21 and accompanied by a modulation of lipid metabolism-related genes in these tissues. 20,[22][23] We also found that oil red O-stainable lipid was increased in the liver (unpublished observations) as well as in the kidney and heart of the rat model of metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 99%
“…21 The latter is particularly intriguing because the cardiac TG pool can be turned over rapidly 28 and may contribute to the metabolic fate of fatty acids. 29 Our data does not support the proposed protective role of cardiac TG which stores toxic lipid metabolites. 30 The apparent contradiction between studies may be attributable to our limited knowledge of how TG synthesis, hydrolysis and turnover are regulated in the heart.…”
contrasting
confidence: 86%
“…The mitochondrial origin of increased superoxide remains controversial because direct measurements of mitochondrial superoxide production showed no increase in STZ hearts (Herlein et al, 2009 (Lopaschuk et al, 1983;Flarsheim et al, 1996;Hattori et al, 2000;Choi et al, 2002;Zhao et al, 2006;Suarez et al, 2008). Furthermore, several studies have demonstrated increased connective tissue content in STZ-diabetic hearts, which can be attenuated by treatment of mice with the aldosterone antagonist spironolactone, suggesting that increased aldosterone action may contribute to cardiac fibrosis (Miric et al, 2001;Westermann et al, 2007;Singh et al, 2008;Ueno et al, 2008;Van Linthout et al, 2008). Cardiac angiotensin II receptor density and synthesis is increased in STZ hearts, and increased superoxide production, apoptosis and fibrosis can be inhibited, at least partially, by treatment with angiotensin receptor blockers or angiotensinconverting enzyme (ACE) inhibitors (Brown et al, 1997;Singh et al, 2008).…”
Section: Disease Models and Mechanisms Dmmmentioning
confidence: 99%